An introduction to international criminal law and procedure - Cryer, Robert; Robinson, Darryl; Vasiliev, Sergey (Cambridge: Cambridge University Press, 2024)
Written by a team of international lawyers with extensive academic and practical experience of international criminal law, the fourth edition of this leading textbook offers readers comprehensive coverage and a high level of academic rigour while maintaining its signature accessible and engaging style. Introducing the readers to the fundamental concepts of international criminal law, as well as the domestic and international institutions that enforce that law, this book engages with critical questions, political and moral challenges, and alternatives to international justice. Suitable for undergraduate and postgraduate students, academics and practitioners in the field, and cited by the International Criminal Tribunal for Yugoslavia, the International Criminal Court, the Special Court for Sierra Leone, the Extraordinary Chambers in the Courts of Cambodia, and the highest courts in domestic systems, this book is a must-read for anyone interested in learning more about international criminal law.
Keywords: International criminal law; International crimes; Criminal procedure (International law); International criminal courts